2020
DOI: 10.1080/21870764.2020.1868080
|View full text |Cite
|
Sign up to set email alerts
|

Design and characterization of ceramic hollow fiber membrane derived from waste ash using phase inversion-based extrusion/sintering technique for water filtration

Abstract: Ismail (2021) Design and characterization of ceramic hollow fiber membrane derived from waste ash using phase inversionbased extrusion/sintering technique for water filtration,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…In addition, the resulting films were compared with those made from kaolin alone or kaolin, and it was found that the extruded films were more permeable and could achieve higher pressures, even with lower porosity. Recent studies on extrusion methods have aimed to use low-cost materials to replace other metal oxides, and studies have been conducted on the use of low-cost membranes to treat oily wastewater and remove heavy metal ions from wastewater [30][31][32][33][34][35][36]. In recent years, Kamoun et al [37] have used Tunisian clay as a raw material and graphite as a porogenic agent to obtain low-cost ceramic tubular membranes by extrusion molding.…”
Section: Extrusion Methodsmentioning
confidence: 99%
“…In addition, the resulting films were compared with those made from kaolin alone or kaolin, and it was found that the extruded films were more permeable and could achieve higher pressures, even with lower porosity. Recent studies on extrusion methods have aimed to use low-cost materials to replace other metal oxides, and studies have been conducted on the use of low-cost membranes to treat oily wastewater and remove heavy metal ions from wastewater [30][31][32][33][34][35][36]. In recent years, Kamoun et al [37] have used Tunisian clay as a raw material and graphite as a porogenic agent to obtain low-cost ceramic tubular membranes by extrusion molding.…”
Section: Extrusion Methodsmentioning
confidence: 99%
“…In the study by Tai et al (2021), an empty fiber ceramic membrane was developed using palm oil fuel ash to be used in the treatment of oily wastewater [43]. The palm oil fuel ash used in the study was obtained from a crude oil palm mill.…”
Section: 5other Wastesmentioning
confidence: 99%